2016
DOI: 10.5194/hess-20-1885-2016
|View full text |Cite
|
Sign up to set email alerts
|

Travel-time-based thermal tracer tomography

Abstract: Abstract. Active thermal tracer testing is a technique to get information about the flow and transport properties of an aquifer. In this paper we propose an innovative methodology using active thermal tracers in a tomographic setup to reconstruct cross-well hydraulic conductivity profiles. This is facilitated by assuming that the propagation of the injected thermal tracer is mainly controlled by advection. To reduce the effects of density and viscosity changes and thermal diffusion, early-time diagnostics are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 54 publications
0
48
0
Order By: Relevance
“…This layer is also visible in the tomogram at the same depth but is thicker. The cause of this difference may be that thermal tracer tomography tends to reduce high-K and increase low-K zones [Somogyv ari et al, 2016]. The inversion by Jim enez et al [2016] was also performed jointly with slug tests, and the slug test profile indicated a very thin sand layer at 390 m (see Figure 8).…”
Section: 1002/2017wr020543mentioning
confidence: 99%
See 1 more Smart Citation
“…This layer is also visible in the tomogram at the same depth but is thicker. The cause of this difference may be that thermal tracer tomography tends to reduce high-K and increase low-K zones [Somogyv ari et al, 2016]. The inversion by Jim enez et al [2016] was also performed jointly with slug tests, and the slug test profile indicated a very thin sand layer at 390 m (see Figure 8).…”
Section: 1002/2017wr020543mentioning
confidence: 99%
“…As a result, the mean tracer velocity distribution (velocity tomogram) is obtained, which can then be converted to a K-field (K-tomogram) according to equation (1). Instead of solving the problem over a regular grid, the staggered grid method is applied in this study [Vesnaver and Bo€hm, 2000] in line with related travel time-based hydraulic tomography applications [Jim enez et al, 2013;Hu et al, 2015;Somogyv ari et al, 2016]. The inverse problem is solved over multiple coarse grids, shifted horizontally and vertically.…”
Section: Travel Time-based Tomographymentioning
confidence: 99%
“…A staggering technique is applied to the inversion procedure for improving the resolution of the final tomogram, and to weaken the effect of positioning (Vesnaver and Böhm, 2000;Somogyvári et al, 2016). The base model used for the inversion is discretized by five columns and four rows.…”
Section: Inversion Of Hydraulic Traveltimesmentioning
confidence: 99%
“…They are based on the inversion of signals that are recorded among multiple sources and receivers, which are employed to infer two-dimensional (2D) or three-dimensional (3D) images of the spatial hydraulic parameter distribution. For identifying those structural characteristics that are relevant for groundwater flow, solute, and heat transport, invasive concepts are available that apply hydraulic [1][2][3][4][5][6] or pneumatic pressure [7][8][9][10], or that use tracers, such as dye [11][12][13], salt [14][15][16][17], or heat tracers [18][19][20][21]. In comparison to many alternative near-surface geophysical applications, these signals are rarely introduced from the ground surface.…”
Section: Introductionmentioning
confidence: 99%